IMPLEMENTASI MODEL PEMBELAJARAN BCCT (BEYOND CENTERS AND CIRCLE TIME) DI TK ISLAM AL-AZHAR BSD - LENY LENY (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2022)
This study aims to describe how the implementation of the BCCT (Beyond Centers and Circle Time) learning model that has been implemented in Group A Kindergarten Islamic Kindergarten Al Azhar BSD, which is located at Jalan Puspita Loka Sector 3.2 BSD, Kelurahan Lengkong Gudang, Serpong District, South Tangerang. -Banten. Using qualitative descriptive research methods. This study uses data and documentation to support the validity of the research results. The observed components consist of; the philosophy of implementing the BCCT/central learning model in Al-Azhar Islamic Kindergarten BSD, strategies for implementing the BCCT/centra learning model in Al-Azhar Islamic Kindergarten BSD, media and infrastructure in implementing the BCCT/centra learning model in Al-Azhar Islamic Kindergarten BSD, the role of teachers in implementing the BCCT/central learning model at Isam Al-Azhar Kindergarten BSD, policies for implementing the BCCT/centra learning model at Al-Azhar Islamic Kindergarten BSD, and evaluating the BCCT/centra learning model at Al-Azhar Islamic Kindergarten BSD. Based on the data obtained from CW1 to CW8, CD1 to CD8 and CO1 to CO 14, it is known that the reason for the application of the learning center model carried out at the Al-Azhar Islamic Kindergarten BSD is because this model is considered very good for building students' knowledge so that children can develop better. . The implementation of center activities adopts the BCCT model developed by Dr. Helen Parkhurst, where center classes are arranged in a special room for each type of center. However, in the selection and naming of centers carried out at Al-Azhar Islamic Kindergarten BSD, it was adjusted to school policy so that it opened eight centers including: Imtaq Center, Beam Center, OTM Center, Preparation Center, Role Playing Center, Arts and Creativity Center, English and Language Center. The Science Center, is slightly different from the implementation of the center in the BCCT main model, namely carrying out seven centers including the Preparation Center, Beam Center, Large Role Playing Center, Small Role Playing Center, Natural Materials Center, Art Center and Imtaq Center. So from the results of the study it was found that Al-Azhar Islamic Kindergarten BSD has implemented the BCCT/Sentra learning model, but it is still semi-central because there are slight differences with the Dalton system designed by Dr, Helen Parkurst, United States which in its implementation is still influenced by factors school policy. ABSTRAKPenelitian ini bertujuan untuk menggambarkan bagaimana implementasi model pembelajaran BCCT (Beyond Centers and Circle Time) yang telah dilaksanakan pada Kelompok A Taman Kanak-kanak TK Islam Al Azhar BSD, yang beralamat di jalan Puspita Loka Sektor 3.2 BSD, Kelurahan Lengkong Gudang Kecamatan Serpong Tangerang Selatan-Banten. Menggunakan metode penelitian deskriptif kualitatif. Penelitian ini menggunakan data dan dokumentasi dalam mendukung keabsahan hasil penelitiannya. Komponen yang diamati terdiri dari; filosofi implementasi model pembelajaran BCCT/sentra di TK Islam Al-Azhar BSD, strategi implementasi model pembelajaran BCCT/sentra di TK Islam Al-Azhar BSD, media sarana dan prasarana dalam implementasi model pembelajaran BCCT/sentra di TK Islam Al-Azhar BSD, peran guru dalam implementasi model pembelajaran BCCT/sentra di TK Isam Al-Azhar BSD, kebijakan implementasi model pembelajaran BCCT/sentra di TK Islam Al-Azhar BSD, dan evaluasi model pembelajaran BCCT/ sentra di TK Islam Al-Azhar BSD. Berdasarkan data yang didapat dari CW1 s.d CW8, CD1 s.d CD8 dan CO1 s.d CO 14, diketahui alasan penerapan model pembelajaran sentra yang dilaksanakan di TK Islam Al-Azhar BSD dikarenakan model ini dirasa sangat baik untuk membangun pengetahuan anak didik sehingga anak dapat berkembang lebih baik. Pelaksanaan kegiatan sentra mengadopsi model BCCT yang dikembangkan oleh Dr. Helen Parkhurst, di mana kelas sentra disusun dalam ruangan khusus untuk setiap jenis sentranya. Namun dalam pemilihan dan penamaan sentra yang dilaksanakan di TK Islam Al-Azhar BSD disesuaikan dengan kebijakan sekolah sehingga membuka delapan sentra diantaranya: Sentra Imtaq, Sentra Balok, Sentra OTM, Sentra Persiapan, Sentra Bermain Peran, Sentra Seni dan Kreativitas, Sentra bahasa Inggris dan Sentra Sains, sedikit berbeda dengan pelaksanaan sentra pada model induk BCCT yaitu melaksanakan tujuh sentra diantaranya Sentra Persiapan, Sentra Balok, Sentra Main Peran Besar, Sentra Main Peran Kecil, Sentra Bahan Alam, Sentra Seni dan Sentra Imtaq. Sehingga dari hasil penelitian didapatkan bahwa TK Islam Al-Azhar BSD telah mengimplementasikan model pembelajaran BCCT/ Sentra, akan tetapi masih bersifat semi sentra karena terlihat adanya sedikit perbedaan dengan sistem Dalton yang dirancang oleh Dr, Helen Parkurst Amerika Serikat yang dalam pelaksanaanya masih dipengaruhi oleh faktor kebijakan sekolah.